Association of major postoperative wound and anastomotic complications in thoracic surgery with COVID-19 infection - Kajetan Kiełbowski; Małgorzata Wojtyś, MD, PhD; Konstantinos Kostopanagiotou, MD, PhD; Henryk Janowski, MD, PhD; Janusz Wójcik, MD, PhD (Surgery Open Science, 2022)
Background: One of the most uncommon manifestations of perioperative Covid-19 infection is impaired wound healing. The aim of this study is to present previously unreported observation of thoracotomy and esophageal anastomosis dehiscence in the course of Covid-19 infection after uncomplicated thoracic surgeries. Methods: This is a single-center study describing unusual wound and anastomosis complications in COVID-19 patients after uncomplicated thoracic surgeries. Medical data was prospectively collected and retrospectively reviewed. All patients admitted to the hospital were symptom free and tested negative for COVID-19 infection preoperatively. Clinical courses were compared to a non-infected control group from historical data. Results: The total of 14 patients were included. Study group involved 7 patients with major wound and anastomosis complications concurrent with COVID-19 infection. Control group was composed of 7 patients matched with the type of surgeries and treated before Coronavirus pandemic. Surgeries included lung transplantations, lung cancer surgeries and esophagectomies. The mean age of the study group was 65.7 years. Major wound and anastomosis complications occurred 13.6 days postoperatively while the mean time of Covid-19 detection was 21 days. The course of infection varied from mild to very severe which resulted in 3 deaths due to COVID-19 induced ARDS. The mean time of hospital stay was 40,9 days. There were no differences between both groups in baseline characteristics while hospitalization time was significantly longer in the study group. Conclusions: COVID-19 infection should be included in differential diagnosis in postoperative patients with major wound or anastomosis complications.